Analysis of the Effectiveness of Tax Amnesty Policy Implementation According to Law Number 11 Year 2016 - Wulan, Chandra; Ahmad, Suparji; Lutfi, Anas (Justice Voice, 2023)
Tax amnesty is a tax write-off that is actually owed without being subject to tax administrative sanctions or criminal sanctions in the field of taxation. Based on Law Number 11 of 2016, tax amnesty is the elimination of taxes that should be owed, not subject to tax administrative sanctions and criminal sanctions in the field of taxation, by declaring assets and paying ransom. The research method used is normative juridical research. The data in this research emphasizes statutory norms that are relevant to the problems of this research. The results of this study indicate that the non-compliance of tax coverage in paying taxes does not escape the sense of public trust in the government. The author argues that the government must be able to be more solutive to increase public tax payments from year to year, where the success of tax payments can effectively accelerate national development by considering the mandate of Pancasila related to social justice for all Indonesian people.